Post-Occupancy Evaluation of a Crisis Shelter Garden and Application of Findings Through the Use of a Participatory Design Process. - Lygum, Victoria L.; Poulsen, Dorthe V.; Djernis, Dorthe; Djernis, Hanne G.; Sidenius, Ulrik; Stigsdotter, Ulrika K. (Health Environments Research & Design Journal (HERD) (Sage Publications, Ltd.))
Objective: This study concerned optimization of an evidence-based crisis shelter garden as a setting for everyday activities and nature-based therapy. The study hereby tested the design guidelines that the garden is based on. Background: Design guidelines for gardens intended to support health are becoming increasingly specialized, targeting different user groups. This study contributes to the knowledge concerning health-supporting garden design at crisis shelters for women and children who are exposed to domestic violence. Method: The study included a post-occupancy evaluation (POE) consisting of landscape analyses, observation of physical traces, and interviews as well as a subsequent participatory design process. Results: The landscape analyses and the observation of physical traces indicated a minimal level of maintenance and recurrent use being limited to a few areas of the garden. The interviews added nuance and new issues to these results, resulting in the following themes: maintenance, accessibility, safety, therapeutic setting and free space, many ways to play, and social and private spheres. The participatory design process led to an optimization of the garden, including changes to its physical design related to making the garden safer, positively distractive, and more versatile in terms of activities. Improvements were also made regarding policy for use, maintenance, and informing users. Conclusion: The design guidelines were tested, and the evidence was strengthened, adding nuance and new issues to consider during further development of the guidelines. Both the POE and the participatory design process were confirmed as crucial aspects of evidence-based health design.